Ventricular Assist Device in Single‐Ventricle Heart Disease and a Superior Cavopulmonary Anastomosis. Issue 2 (6th July 2015) - Niebler, Robert A.; Shah, Tejas K.; Mitchell, Michael E.; Woods, Ronald K.; Zangwill, Steven D.; Tweddell, James S.; Berger, Stuart; Ghanayem, Nancy S.
Abstract: Our objective is to describe the use of a ventricular assist device (VAD) in single‐ventricle patients with circulatory failure following superior cavopulmonary anastomosis (SCPA). We performed a retrospective chart review of all single‐ventricle patients supported with a VAD following SCPA. Implantation techniques, physiologic parameters while supported, medical and surgical interventions postimplant, and outcomes were reviewed. Four patients were supported with an EXCOR Pediatric (Berlin Heart Inc., The Woodlands, TX, USA) following SCPA for a median duration of 10.5 days (range 9–312 days). Selective excision of trabeculae and chords facilitated apical cannulation in all patients without inflow obstruction. There were two pump exchanges in the one patient supported for 312 days. Two patients were evaluated by cardiac catheterization while supported. Three of four patients were successfully bridged to transplantation. One patient died while supported. All patients had significant bleeding at the time of transplantation, and one required posttransplant extracorporeal membrane oxygenation with subsequent full recovery. VAD support can provide a successful bridge to transplantation in patients with single‐ventricle circulation following SCPA. A thorough understanding of the challenges encountered during this support is necessary for successful outcomes.